2002
DOI: 10.1029/2001gc000159
|View full text |Cite
|
Sign up to set email alerts
|

Alkenone distributions in the North Atlantic and Nordic sea surface waters

Abstract: [1] The C 37 -C 39 alkenones were quantified in suspended particulate matter obtained from the surface waters of the North Atlantic, including the Nordic seas, over a temperature range of 4°-20°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 34 publications
6
95
1
1
Order By: Relevance
“…In fact, the alkenone distributions in Qinghai are more similar to those from northern high-latitude oceans than to those in lakes (Figure 2). %C 37:4 in Lake Qinghai varies between 15-45%, similar to the range found in the Nordic Sea [Sicre et al, 2002].…”
Section: Alkenone Distribution In Lake Qinghaimentioning
confidence: 53%
See 3 more Smart Citations
“…In fact, the alkenone distributions in Qinghai are more similar to those from northern high-latitude oceans than to those in lakes (Figure 2). %C 37:4 in Lake Qinghai varies between 15-45%, similar to the range found in the Nordic Sea [Sicre et al, 2002].…”
Section: Alkenone Distribution In Lake Qinghaimentioning
confidence: 53%
“…In ocean and other lakes, U 37 k 0 is negatively correlated with %C 37:4 [Sicre et al, 2002;Thiel et al, 1997;Zink et al, 2001] However, in Lake Qinghai, U 37 k 0 is positively correlated with %C 37:4 . In other words, the relative importance of C 37:4 to C 37:3 increases or decreases Figure 1.…”
Section: Alkenone Distribution In Lake Qinghaimentioning
confidence: 76%
See 2 more Smart Citations
“…[12] Modern calibration exercises have demonstrated that high %C 37:4 values in both particulate organic matter and surface sediments are associated with low-temperature and low-salinity surface water masses of the Arctic and Polar Water domains [Bendle and Rosell-Melé, 2004;Bendle et al, 2005;Harada et al, 2006;Sicre et al, 2002]. Thus, %C 37:4 in sediments exceeds 5% below Arctic Atlantic Waters (north of the Arctic Front, delineated using the 35 p.s.u.…”
Section: Evaluation Of the Alkenone Proxy Recordsmentioning
confidence: 99%